Enterococcus Species Isolated from Northern Bobwhite (Colinus virginianus) Chicks: Species Distribution and Antibiotic Resistance - McMurphy, Martha A.; Applegate, Roger D.; Crupper, Scott S. (International Journal of Poultry Science, 2009)
Intestinal fragments from newly hatched to seven-day-old Northern Bobwhite chicks (n = 39) were processed to isolate organisms belonging to the genus Enterococcus. Identification of the eighty-nine enterococci revealed forty-two E. saccharolyticus, twenty E. malodoratus, eight E. pseudoavium, seven E. raffinosus, six E. faecalis, two E. mundtii, two E. avium, one E. cecorum and one E. durans. Each isolate was examined for its resistance to ampicillin, ciprofloxacin, clindamycin, erythromycin, nitrofurantoin, tetracycline, and vancomycin by the disk diffusion assay. Our results indicate all isolates were resistant to at least two of the antibiotics examined, sixty-nine were resistant to three different antibiotics, while sixteen isolates were resistant to four of the seven antibiotics examined. Most significantly, eighteen enterococcal isolates, five of which were E. faecalis, were shown to be vancomycin resistant and possess a minimal inhibitory concentration of >160 μg/ml. In many of the isolates, the genetic location of the antibiotic resistance genes was shown to be present on conjugative plasmids.